Upper Gastrointestinal Manifestation of Bezoars and the Etiological Factors: A Literature Review - Samiullah Khan; Kui Jiang; Lan-ping Zhu; Iftikhar-ahmad Khan; Kifayat Ullah; Saima Khan; Xin Chen; Bang-mao Wang (Gastroenterology Research and Practice)
A gastric bezoar is a compact mass of indigestible foreign materials that accumulate and consolidate in the stomach; however, it can be found in other sites of the gastrointestinal tract. The causative manner of this condition is complex and multifactorial. The main purpose of the review was to raise awareness among clinicians, particularly gastroenterologists, that patients with certain risk factors or comorbid conditions are predisposed to gastric bezoar formation. Early diagnosis and prompt intervention are crucial to avoid bezoar-induced complications. Upper gastrointestinal endoscopy is the standard diagnostic and therapeutic method for gastric bezoars. However, for large size bezoars, surgical intervention is needed.